Frontal Sinus Fractures: Anterior Skull Base - Klotch, Douglas W. (Facial Plastic Surgery, 2000)
The frontal sinus is fractured in 30% of patients sustaining maxillofacial injury. The CT scan has simplified the treatment plan allowing the surgeon to be more selective in the treatment choice, surgical approach, and follow-up. Fractures may involve the anterior, posterior, or both tables of the sinus. The frontal sinus repair or surgery takes place when there is minimal displacement and the frontal ducts are in tact. Obliteration of the sinus is suggested when the ducts are injured, but there is no significant bone loss or comminution of the posterior table. More extensive injuries of the posterior table require cranialization. The mucosa of the sinus must be reviewed completely, sealing off the nasal cavity to help decrease mucocele formation and other intracranial complications. Tedius repair of the dura (pericranial flap) decrease persistent CSF leak and intercranial infections. The anterior table must always be carefully repaired to optimize the cosmetic result. Careful follow-up is required to direct potential mucocele formation or delayed or persistent CSF leak. Judicious use of posteroperative scars help to confirm these diagnosis.
Keywords: sinus fractures; obliteration; cranialization; CSF leak; mucocele